Right upper lobe segmentectomy and subsegmentectomy guided by classification pattern of peripheral segmental veins - Li, Zhikai; Chen, Shuangqing; Ren, Dahu; Kong, Yuhong; Xu, Shun; Duan, Guochen; Zhang, Xiaopeng (Frontiers in Oncology, 2023)
Abstract Background: Studies have analyzed the simplified branching pattern of peripheral segmental veins and developed a standardized approach for intersegmental vein identification in the right upper lobe (RUL). However, the identification approach of intersubsegmental veins has not been reported. This study aimed to supplement the identification approach of intersubsegmental veins and the classification pattern of peripheral segmental veins by using three-dimensional computed tomography bronchography and angiography (3D-CTBA). Materials and Methods: A total of 600 patients with ground glass opacity (GGO) who had undergone 3D-CTBA preoperatively at Hebei General Hospital between September 2020 and September 2022 were used for the retrospective study. We reviewed the anatomical variations of RUL veins in these patients using 3D-CTBA images. Results: According to the anatomical position, the peripheral segmental veins structures of RUL were classified into five categories: “Iab type of anterior with central vein” (256/600, 42.7%), “Ib type of anterior with central vein” (166/600, 27.7%), “Central vein type” (38/600, 6.3%), “Anterior vein type” (81/600, 13.5%), “Right top pulmonary vein type” (57/600, 9.5%). The approach for intersegmental vein and intersubsegmental veins identification was divided into five types: anterior approach, posterobronchial approach, central vein approach, V2t approach, and intermediate bronchus posterior surface approach. Conclusions: The classification pattern of peripheral segmental veins should find wide application. Further, approaches identifying intersegmental veins and intersubsegmental veins may help thoracic surgeons perform safe and accurate RUL segmentectomy. Keywords: right upper lobe (RUL), vein variations, classification, identification approach, segmentectomy, lobectomy, non-small cell lung carcinoma (NSCLC), video-assisted thoracoscopic surgery (VATS).